2004
DOI: 10.1103/physrevb.69.153301
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise of spin current

Abstract: We report an exact solution for the noise spectrum of spincurrent without charge-current in a spin field effect transistor (SFET). For the SFET with two leads, it is found that both auto-and cross-correlation functions are needed to characterize the noise of spin-current. A shot noise is also generated for the charge-current even though the net chargecurrent is identically zero. The noise spectra of spin-current and charge-current depends on the coupling strength between the SFET and the leads, and they may be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 28 publications
7
52
0
Order By: Relevance
“…For instance, the shot noise of spin current in a spin pump device was analyzed based on the Keldysh nonequilibrium Green-function method. 18 It is shown that the spincurrent shot noise can also be used to probe quantum correlation effect in a four terminal geometry with Rashba effect. 19 The possibility of using the spin-current shot noise to measure the spin-relaxation time has been theoretically proposed.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the shot noise of spin current in a spin pump device was analyzed based on the Keldysh nonequilibrium Green-function method. 18 It is shown that the spincurrent shot noise can also be used to probe quantum correlation effect in a four terminal geometry with Rashba effect. 19 The possibility of using the spin-current shot noise to measure the spin-relaxation time has been theoretically proposed.…”
Section: Introductionmentioning
confidence: 99%
“…It should be also noted that the problem of spin shot noise has been already considered in many papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and for various systems. The main interest of these works was focused on how the discreteness of spin affects the current fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Since electrons carry spin, the discreteness of spin carriers fluctuates during their transport and the statistical behavior results in the spin current noise. The theoretical investigation on spin current without an accompanying charge current has been reported recently for the system under a rotating magnetic field [38]. The shot noise of spin polarized electrons has been shown to be dependent on spin-flip processes [39].…”
mentioning
confidence: 98%